2018
DOI: 10.3390/en11123455
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Natural Laccase Redox Mediators in Simultaneous Dye Decolorization and Power Production in Microbial Fuel Cells

Abstract: Redox mediators could be used to improve the efficiency of microbial fuel cells (MFCs) by enhancing electron transfer rates and decreasing charge transfer resistance at electrodes. However, many artificial redox mediators are expensive and/or toxic. In this study, laccase enzyme was employed as a biocathode of MFCs in the presence of two natural redox mediators (syringaldehyde (Syr) and acetosyringone (As)), and for comparison, a commonly-used artificial mediator 2,2 -azinobis(3-ethylbenzthiazoline-6-sulfonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…There are various studies that have investigated azo dye decolourization in the anode and others in the cathode (Huang et al, 2017;Lai et al, 2017;Mani et al, 2018). It is not clear which approach is the best as different studies used different organisms, operating conditions, cathode catalyst etc., making a direct comparison of decolourization rates for each system difficult ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…There are various studies that have investigated azo dye decolourization in the anode and others in the cathode (Huang et al, 2017;Lai et al, 2017;Mani et al, 2018). It is not clear which approach is the best as different studies used different organisms, operating conditions, cathode catalyst etc., making a direct comparison of decolourization rates for each system difficult ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Lac stability and activity was decreased when incubated with arti cial these redox mediators in the long run. us, natural mediators have been used due to their environmental friendliness, low-cost, and good biocompatibility to laccase [38].…”
Section: Catalyticmentioning
confidence: 99%
“…Therefore, natural resources or products were recently considered to replace such artificially synthesized compounds for sustainable applications. Several studies clearly revealed that appropriate supplementation of natural products abundant in electrochemically active substances could significantly promote simultaneous bioelectricity generation and wastewater treatment in MFCs [17] , [18] , [19] , [20] . Recently, Xu et al [20] extracted natural herbal substances abundant in anthocyanins to effectively increase nearly threefold efficiency of bioelectricity generation in MFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Xu et al [20] extracted natural herbal substances abundant in anthocyanins to effectively increase nearly threefold efficiency of bioelectricity generation in MFCs. From the perspective of chemical structure, in fact these bioelectricity-stimulating substances were mostly polyphenols, which are abundant in natural plants [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation